Community Knowledge, Attitude, and Preventive Practice for Cutaneous Leishmaniasis in an Endemic Region, Northeastern Iran - Pourmohammadi , Behrad; Rohani-Rasaf, Marzieh (Shahroud Journal of Medical Sciences, 2024)
Background: Knowing the level of awareness, attitude, and performance of people is an important step in leishmaniasis prevention. This study aimed to investigate the knowledge, attitude, and practice of people in Damghan district about cutaneous leishmaniasis in 2018-2020.Methods: In this cross-sectional descriptive study, for 500 people living in urban and rural areas, a semi-structured researcher-made questionnaire approved for content validity and reliability was randomly completed by a trained questionnaire and information was recorded and analyzed using SPSS21 software.Results: The mean age of the subjects was 37.7, and 52.6% of them were in the age group of 20-40 years. 55% of people had poor knowledge, and 61% and 65% had moderate attitudes and performance, respectively. 97.2%, 72%, and 32.4% of the subjects did not know the agent, reservoir, and symptoms of the disease, respectively. To prevent the disease; 44.6% of people did not take any action, 54.2% installed nets on doors and windows, and also 28.5%, 40.2%, and 25.3%, respectively, always used mosquito nets, insecticide sprays, and insect repellent ointments.Conclusions: Despite being the disease endemic in the region, the level of knowledge, attitude, and practice of the people was weak to moderate. Therefore, raising the KAP levels of the county's people about leishmaniasis is highly recommended.